2013
DOI: 10.1371/journal.pone.0069760
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Eicosapentaenoic Acid Decreases CD133 Colon Cancer Stem-Like Cell Marker Expression While Increasing Sensitivity to Chemotherapy

Abstract: Colorectal cancer is the third leading cause of cancer-related death in the western world. In vitro and in vivo experiments showed that omega-3 polyunsaturated fatty acids (n-3 PUFAs) can attenuate the proliferation of cancer cells, including colon cancer, and increase the efficacy of various anticancer drugs. However, these studies address the effects of n-3 PUFAs on the bulk of the tumor cells and not on the undifferentiated colon cancer stem-like cells (CSLCs) that are responsible for tumor formation and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 61 publications
(79 reference statements)
0
49
0
Order By: Relevance
“…In the same context, De Carlo et al reported that EPA increases the sensitivity of COLO 320 DM cells to both drugs 5-FU+Oxaliplatin. EPA also increased the sensitivity of the CSLCs-bearing colon cancer marker CD133 to 5-FU [127].…”
Section: Colorectal Cancermentioning
confidence: 89%
“…In the same context, De Carlo et al reported that EPA increases the sensitivity of COLO 320 DM cells to both drugs 5-FU+Oxaliplatin. EPA also increased the sensitivity of the CSLCs-bearing colon cancer marker CD133 to 5-FU [127].…”
Section: Colorectal Cancermentioning
confidence: 89%
“…ω3 EPA also decreased markers of CD133 + colon cancer stem-like cells (CSLCs) while increases the sensitivity to chemotherapy [89]. A Phase II double-blind, placebo-controlled trial of EPA-FFA in patients undergoing liver resection surgery for CRC liver metastases (CRCLM) showed that EPA-FFA therapy has antiangiogenic properties and is safe and well tolerated [90].…”
Section: Lipidome In Clinical Trials For Crcmentioning
confidence: 99%
“…Thus, novel anticancer strategies have been designed to selectively target CSC, and to this purpose, natural compounds, including ω3 PUFA, might have a relevant role. In colon cancer stem-like cells (CSLC), De Carlo et al showed that EPA has a pre-differentiating effect and this finding could, at least in part, explain the increased cellular sensitivity to 5-FU (82). In keeping with these observations, Yang and colleagues demonstrated that EPA and DHA, in a single or combined treatment, enhanced the chemotherapeutic sensitivity effect of 5-FU and mitomycin C by inducing apoptotic cell death of CSLC (83).…”
Section: ω3 Pufa As Potential Adjuvants In the Therapy Of Crcmentioning
confidence: 99%